2015
DOI: 10.1210/en.2014-1673
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Inhibit the Osteogenic Response to Mechanical Loading in Adult Male Mice

Abstract: Androgens are well known to enhance exercise-induced muscle hypertrophy; however, whether androgens also influence bone's adaptive response to mechanical loading remains unclear. We studied the adaptive osteogenic response to unilateral in vivo mechanical loading of tibia in adult male mice in both a long- and a short-term experimental set-up. Mice were divided into four groups: sham operated, orchidectomized (ORX), T (ORX+T), or nonaromatizable dihydrotestosterone (ORX+DHT) replacement. Significant interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 63 publications
(66 reference statements)
2
30
0
Order By: Relevance
“…However, once sclerostin had been shown to be expressed in osteocytes [9], Robling et al [16] convincingly demonstrated that one potentially important mechanism by which mechanical loading controls osteocyte activity is by regulating sclerostin expression. His demonstration that loading the mouse ulna down regulates sclerostin expression has been reproduced in a variety of experimental loading models [17], [18], [19], [20], [21], [22], [23] (Fig. 1).…”
Section: Introductionmentioning
confidence: 88%
“…However, once sclerostin had been shown to be expressed in osteocytes [9], Robling et al [16] convincingly demonstrated that one potentially important mechanism by which mechanical loading controls osteocyte activity is by regulating sclerostin expression. His demonstration that loading the mouse ulna down regulates sclerostin expression has been reproduced in a variety of experimental loading models [17], [18], [19], [20], [21], [22], [23] (Fig. 1).…”
Section: Introductionmentioning
confidence: 88%
“…They injected FITC-labeled bovine serum albumin tracer into rats’ tibia during loading and demonstrated that the load-induced solute transport around osteocyte was enhanced in ovariectomized animals (48). Another study reported that androgens inhibits osteogenic responses to mechanical loading in adult male mice (49) demonstrating a close relationship between sex hormones and skeletal mechanobiology.…”
Section: Osteocytes’ Mechano-transductionmentioning
confidence: 97%
“…Thus, Callewaert et al[45] found that loading induced significantly more periosteal bone formation in male androgen receptor knock out (ARKO) as compared with WT mice and had a stronger inhibitory effect on sclerostin expression in ARKO vs WT mice. In a subsequent study, Sinnesael et al [46] found that testosterone treatment of orchiectomized mice increased the number of sclerostin-positive osteocytes. In contrast to these findings, Di Nisio et al [29] found that dihydrotesterone (DHT) decreased sclerostin expression in cultured human osteocytes, suggesting that the in vitro (direct) effects of androgens may differ from their in vivo (perhaps indirect) effects on sclerostin production.…”
Section: Hormonal Regulation Of Sclerostinmentioning
confidence: 99%